Potential Work-related Exposure to SARS-CoV-2 by Standard Occupational Grouping Based on Pre-lockdown Working Conditions in France - Narges Ghoroubi; Emilie Counil; Myriam Khlat (Elsevier, 2023)
This study aims to ascertain occupations potentially at greatest risk of exposure to SARS-CoV-2 based on pre-lockdown working conditions in France. We combined two French population-based surveys documenting workplace exposures to infectious agents, face-to-face contact with the public, and working with colleagues just before the pandemic. Then, for each 87-level standard French occupational grouping, we estimated the number and percentage of the French working population reporting these occupational exposure factors, by gender, using survey weights. As much as 40% (11 million) of all workers reported at least two exposure factors. Most of the workers concerned were in the healthcare sector. However, army/police officers, firefighters, hairdressers, teachers, cultural/sports professionals, and some manual workers were also exposed. Women were overrepresented in certain occupations with potentially higher risks of exposure such as home caregivers, childminders, and hairdressers. Our gender-stratified matrix can be used to assign prelockdown work-related exposures to cohorts implemented during the pandemic.